Islands within islands: genetic structuring at small spatial scales has implications for long‐term persistence of a threatened species. (20th June 2020) - Major, R. E.; Ewart, K. M.; Portelli, D. J.; King, A.; Tsang, L. R.; O'Dwyer, T.; Carlile, N.; Haselden, C.; Bower, H.; Alquezar‐Planas, D. E.; Johnson, R. N.; Eldridge, M. D. B.
Abstract: Maintenance of genetic diversity within species is a key objective of biodiversity conservation, and small, isolated populations are particularly vulnerable to genetic erosion. Conservation management actions such as predator removal, captive breeding and reintroduction can facilitate numerical recovery of a population, but species often remain at risk from depleted genetic diversity and inbreeding. We investigated dispersal, genetic bottlenecks and genetic population structuring in the island‐dwelling Lord Howe woodhen, a species that came perilously close to extinction in the 1970s. Analyses of mark‐resighting records and variable genetic markers (single‐nucleotide polymorphisms) collected from the contemporary population and 100‐year‐old museum specimens found strong evidence of restricted dispersal at fine spatial scales, with both the contemporary and historic populations exhibiting strong population structuring between mountain and lowland/slopes sites. Additionally, genetic comparison of the contemporary population and historic specimens demonstrated a decline in genetic diversity over the past century. Specifically for the Lord Howe woodhen, we recommend ongoing genetic monitoring and translocations to increase genetic diversity within the re‐established lowland subpopulation. More generally, our results demonstrate how pronounced genetic erosion can arise in species subject to human persecution and predation by introduced predators, and how genetic fragmentation of natural populations can be present at fine geographical scales (less than hundreds of metres). Moreover, without prior information about genetic structure and subsequent genetic monitoring, conservation management can have unexpected negative consequences for the genetic health of populations. Therefore, genetic monitoring and management early in the recovery of populations is desirable to maximize their adaptive potential. Abstract : This study investigated dispersal, genetic bottlenecks and genetic population structuring in the island‐dwelling Lord Howe woodhen, a species that came perilously close to extinction in the 1970s. Analyses of mark‐resighting records and single nucleotide polymorphism genetic markers collected from the contemporary population and 100‐year‐old museum specimens found strong evidence of restricted dispersal at fine spatial scales, with both the contemporary and historic populations exhibiting strong population structuring between mountain and lowland/slopes sites, as well as a decline in genetic diversity over the past century. These findings demonstrate how pronounced genetic erosion can arise in species subject to human persecution and predation by introduced predators, and how genetic fragmentation of natural populations can be present at fine geographical scales. We conclude that genetic monitoring and management early in the recovery of populations is desirable to maximise their adaptive potential.